Application of community counseling through batik ciprat production to foster skills and creativity in persons with disabilities - Mumpuni, Sesya Dias; Mustofa, Zaenal; Firmansah, Firmansah; Susilowati, Novi (Universitas Muhammadiyah Magelang, 2025)
Given the crucial role of inclusive village forums in educating and facilitating the participation of citizens with disabilities, this community service activity aimed to develop skills, enhance creativity, and encourage positive behavioral changes in persons with disabilities through community counseling integrated with the practice of batik ciprat production. Implemented in 10 inclusive village forum communities in Tegal Regency, the program involved the active participation of members with disabilities in module education and hands-on batik ciprat creation, focusing on emotional expression as a form of art therapy and self-healing. The activity's results showed increased knowledge and skills in batik ciprat making among persons with disabilities, while also providing a self-healing effect that contributed to positive behavioral changes and sustainable improvement in quality of life. This inclusive and therapeutic approach proved effective in empowering persons with disabilities.